Non-noble metal-catalyzed cross-dehydrogenation coupling (CDC) involving ether α-C(sp3)–H to construct C–C bonds - Yu, Hui; Xu, Feng (Beilstein Journal of Organic Chemistry, 2023)
Ether derivatives are widespread as essential building blocks in various drugs, natural products, agrochemicals, and materials. Modern economy requires developing green strategies with improved efficiency and reduction of waste. Due to its atom and step-economy, the cross-dehydrogenative coupling (CDC) reaction has become a major strategy for ether functionalization. This review covers C–H/C–H cross-coupling reactions of ether derivatives with various C–H bond substrates via non-noble metal catalysts (Fe, Cu, Co, Mn, Ni, Zn, Y, Sc, In, Ag). We discuss advances achieved in these CDC reactions and hope to attract interest in developing novel methodologies in this field of organic chemistry.
Keywords: alkylation; cross-dehydrogenation coupling; ether; non-noble metals